Effect of Single and Combined Monochromatic Light on the Human Pupillary Light Response - Bonmati-Carrion, Maria A.; Hild, Konstanze; Isherwood, Cheryl M.; Sweeney, Stephen J.; Revell, Victoria L.; Madrid, Juan A.; Rol, Maria A.; Skene, Debra J. (Frontiers in Neurology, 2018)
The pupillary light reflex (PLR) is a neurological reflex driven by rods, cones, and melanopsin-containing retinal ganglion cells. Our aim was to achieve a more precise picture of the effects of 5-min duration monochromatic light stimuli, alone or in combination, on the human PLR, to determine its spectral sensitivity and to assess the importance of photon flux. Using pupillometry, the PLR was assessed in 13 participants (6 women) aged 27.2 ± 5.41 years (mean±SD) during 5-min light stimuli of purple (437nm), blue (479nm), red (627nm), and combinations of red+purple or red+blue light. In addition, nine 5-min, photon-matched light stimuli, ranging in 10nm increments peaking between 420 to 500nm were tested in 15 participants (8 women) aged 25.7±8.90 years. Maximum pupil constriction, time to achieve this, constriction velocity, area under the curve (AUC) at short (0-60s) and longer duration (240-300s) light exposures, and 6-s post-illumination pupillary response (6-s PIPR) were assessed. Photoreceptor activation was estimated by mathematical modelling. The velocity of constriction was significantly faster with blue monochromatic light than with red or purple light. Within the blue light spectrum (between 420 and 500nm), the velocity of constriction was significantly faster with the 480nm light stimulus, while the slowest pupil constriction was observed with 430nm light. Maximum pupil constriction was achieved with 470nm light, and the greatest AUC0-60 and AUC240-300 was observed with 490 and 460nm light, respectively. The 6-s PIPR was maximum after 490nm light stimulus. Both the transient (AUC0-60) and sustained (AUC240-300) response was significantly correlated with melanopic activation. Higher photon fluxes for both purple and blue light produced greater amplitude sustained pupillary constriction. The findings confirm human PLR dependence on wavelength, monochromatic or bichromatic light and photon flux under 5-min duration light stimuli. Since the most rapid and high amplitude PLR occurred within the 460-490nm light range (alone or combined), our results suggest that colour discrimination should be studied under total or partial substitution of this blue light range (460-490nm) by shorter wavelengths (∼440nm). Thus for nocturnal lighting, replacement of blue light with purple light might be a plausible solution to preserve colour discrimination while minimizing melanopic activation.